2020
DOI: 10.3390/catal11010017
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Mechanism for Methane-to-Methanol in Cu-SSZ-13: First-Principles Study of the Z2[Cu2O] and Z2[Cu2OH] Motifs

Abstract: As transportation continues to increase world-wide, there is a need for more efficient utilization of fossil fuel. One possibility is direct conversion of the solution gas bi-product CH4 into an energy-rich, easily usable liquid fuel such as CH3OH. However, new catalytic materials to facilitate the methane-to-methanol reaction are needed. Using density functional calculations, the partial oxidation of methane is investigated over the small-pore copper-exchanged zeolite SSZ-13. The reaction pathway is identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Zeolites are known to be very humid, and the presence of water has proven to be important for reactions in the zeolite. 20,27 The dry mechanism as illustrated in Figure 1 The energy landscape for activation of Z 2 [2Cu], with water included in the reaction, is shown in Figure 2. As opposed to the 2Cu system without H 2 O, inclusion of water initially lifts one of the Cu ions from its position in the 6 MRs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zeolites are known to be very humid, and the presence of water has proven to be important for reactions in the zeolite. 20,27 The dry mechanism as illustrated in Figure 1 The energy landscape for activation of Z 2 [2Cu], with water included in the reaction, is shown in Figure 2. As opposed to the 2Cu system without H 2 O, inclusion of water initially lifts one of the Cu ions from its position in the 6 MRs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Zeolites are known to be very humid, and the presence of water has proven to be important for reactions in the zeolite. , The dry mechanism as illustrated in Figure might, thus, be affected by the addition of H 2 O. Here, one H 2 O is introduced into the reaction mechanism and is allowed to interact with the reaction intermediates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Copper trimers have, for example, been observed in large-pore structures, such as MFI and MOR whereas monomers and dimers predominantly have been observed in small-pore zeolites, such as chabazite (CHA). In addition to the pore size, the number of Cu atoms in the preferred site is believed to be affected by the Si/Al ratio and the distance between the Al ions in the zeolite framework. , The zeolite is at standard conditions humid, and the presence of water has been reported to affect the oxidation properties of the metal site , as well as the mechanism for methane-to-methanol conversion. , Using density functional theory (DFT) calculations in combination with kinetic modeling, we have shown that the presence of water significantly increases the activity of the Cu dimer site in the CHA framework, by increasing the mobility of the Cu cations, lowering reaction barriers, and facilitating the desorption of methanol …”
Section: Introductionmentioning
confidence: 96%
“…16,17 The zeolite is at standard conditions humid, and the presence of water has been reported to affect the oxidation properties of the metal site 18,19 as well as the mechanism for methane-to-methanol conversion. 20,21 Using density functional theory (DFT) calculations in combination with kinetic modeling, we have shown that the presence of water significantly increases the activity of the Cu dimer site in the CHA framework, by increasing the mobility of the Cu cations, lowering reaction barriers, and facilitating the desorption of methanol. 22 A crucial property of the catalytic site is its ability to change the oxidation state, which is required to adsorb O 2 .…”
Section: ■ Introductionmentioning
confidence: 99%